2023
DOI: 10.1002/anie.202302202
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Asymmetric Structure of NH2‐UiO‐66 Metal‐Organic Frameworks for Light‐promoted Selective and Efficient Gold Extraction and Separation

Abstract: Designing adsorption materials with high adsorption capacities and selectivities is highly desirable for precious metal recovery. Desorption performance is also particularly crucial for subsequent precious metal recovery and adsorbent regeneration. Herein, a metalorganic framework (MOF) material (NH 2 -UiO-66) with an asymmetric electronic structure of the central zirconium oxygen cluster has an exceptional gold extraction capacity of 2.04 g g À 1 under light irradiation. The selectivity of NH 2 -UiO-66 for go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The charge density difference (Figure 6c) was calculated to investigate the charge transfer at the Co 3 S 4 / MoS 2 interfaces. [26] 0.892 e À was transferred from MoS 2 to the Co 3 S 4 surface. The blue and yellow isosurfaces represented charge depletion and accumulation, respectively.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The charge density difference (Figure 6c) was calculated to investigate the charge transfer at the Co 3 S 4 / MoS 2 interfaces. [26] 0.892 e À was transferred from MoS 2 to the Co 3 S 4 surface. The blue and yellow isosurfaces represented charge depletion and accumulation, respectively.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The higher ζ-potential of PCN-224 in light led to relatively stronger repulsion to positive nonprecious metal ions, thus showing enhanced selectivity. In summary, we found that visible light largely promoted the Au recovery performance of PCN-224 and made it superior to other materials in terms of recovery capacity ( q max ) and selectivity ( K d ), including UiO-66, COFs, polymers, ,,, and 2D materials ,, (Figure S9).…”
Section: Resultsmentioning
confidence: 90%
“…We also noted that visible light enhanced the selectivity of Au by both increasing the recovery of Au(III) and decreasing the uptake of nonprecious metals. Under light irradiation, the uptake of Zn and made it superior to other materials in terms of recovery capacity (q max ) and selectivity (K d ), including UiO-66, 57 COFs, 58−61 polymers, 37,38,62,63 and 2D materials 33,64,65 (Figure S9).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The prosperity of modern civilization is based on the consumption of a large amount of fossil fuels. However, the consumption of fossil fuels is usually accompanied by the release of a large amount of CO 2 , which has resulted in serious energy and environmental problems. CO 2 photoreduction taking the use of clean solar energy to convert CO 2 into valuable fuels has been considered as one of the most potent means to achieve carbon neutralization without creating new carbon emissions in the whole reaction process. However, the limited light utilization efficiency of pristine photocatalysts and poor charge separation greatly restrict the efficiency of CO 2 photoreduction. , Hitherto, many efforts to enhance the light utilization and charge separation of photocatalysts have been made. …”
Section: Introductionmentioning
confidence: 99%